Du libre accès à l'accès restreint aux écoles anglaises du Québec - Lebel, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
In this article, the author gives a historical account of the different laws enacted by the National Assembly in order to enhance the status of the French language at administrative levels as well as among the province's résidants themselves. The schools, being vehicles of social and cultural influence, were included. Laws 63 and 22 were little more than tentative, hesitant sallies into the linguistic battle confronting the province and its minority groups. Law 101 provided a more coherent line of reasoning in deciding Quebec's language policies. Nevertheless, it is contested by some groups on constitutional grounds.